Evaluation of Waste Management at the Aradkouh Waste Processing Complex, Kahrizak, Tehran - Samadi, Shayan; Ahmadian, Reza (Management Strategies and Engineering Sciences, 2026)
Over the past decade, numerous criticisms have been raised at the national, provincial, and local governmental levels regarding the mismanagement and inefficiency of the Aradkouh waste complex in Kahrizak, Tehran. However, these criticisms have not yet led to any decisive policy-making or concrete actions aimed at resolving this problem. In recent years, municipal authorities have repeatedly addressed issues related to the management of Aradkouh, and the complex has frequently been identified by relevant officials as one of the primary sources responsible for the capital city’s unpleasant odor. The most important indicators for measuring and evaluating waste management performance at Aradkouh include the degree of damage control, the implementation of optimal management practices, and the realization of value-added generation from waste—often referred to as “dirty gold.” Accordingly, this study first conducted a comprehensive assessment of the waste generation cycle in Tehran, followed by an evaluation of waste management practices at the Aradkouh complex as the largest waste management facility in Tehran. Subsequently, strategic evaluation was carried out using benchmarking as the primary analytical method, while technology assessment and SWOT analysis were employed as complementary approaches. Overall, the findings indicate that, compared with global experiences, the current management approach suffers from major deficiencies, including weaknesses in waste control and separation (both at the source and due to incomplete processing at the destination), failure to achieve fully sanitary landfilling, lack of coherent and active infrastructure for energy production (including gas recovery, energy generation, and waste incineration), and the absence of a comprehensive strategic framework.